Diversity of Bryophytes Based on Substrate Types in the Karangkamulyan Tourist Area, Ciamis Regency - Wahyuningsih, Endang Prayudaty; Martiwi, Ika Nugraheni Ari (Jurnal Biologi Tropis, 2025)
Indonesia is renowned as a megabiodiversity country with a wealth of flora, including the diversity of bryophytes. These plants play a crucial role in ecosystems, such as oxygen production, erosion control, and water absorption. This study aims to analyze the diversity of bryophytes in the Karangkamulyan Tourism Area, Ciamis Regency, and to examine their diversity based on substrate types. Karangkamulyan is a cultural and natural conservation area covering 25.5 hectares with a climate and conditions that support bryophyte growth. The research utilized an exploratory method with random sampling at three selected points within the area. Morphological and anatomical analyses were conducted to identify species, and the percentage of occurrence was analyzed based on substrate types. The results revealed the presence of 15 species belonging to 12 families of bryophytes inhabiting various substrates such as soil, rocks, and tree trunks. The identified bryophytes included 6 liverworts (Marchantiophyta): Dumortiera hirsuta, Marchantia emarginata, Riccia gangetica, Heteroscyphus argutus, Heteroscyphus coalitus, and Schiffneriolejeunea sp.; and 9 mosses (Bryophyta): Neckeropsis undulata, Thuidium plumulosum, Ectropothecium falciforme, Fissidens sp., Fissidens flaccidus, Calymperes sp., Hyophila sp., Barbula sp., and Bryum sp. Based on substrate types, 91 occurrences were recorded, consisting of 25% terrestrial bryophytes (23 occurrences), 55% epiphytic bryophytes (50 occurrences), and 20% epilithic bryophytes (18 occurrences).